Characterization, conductivity studies, dielectric properties, and gas sensing performance of in situ polymerized polyindole/copper alumina nanocomposites. Issue 38 (28th February 2020) - Sankar, S.; Naik, Adarsh A.; Anilkumar, T.; Ramesan, M. T.
Abstract: Conducting polymer composites of polyindole (PIN) and copper–alumina (Cu–Al2 O3 ) nanocomposites were synthesized by in situ polymerization of indole with different contents of Cu–Al2 O3 nanoparticles. The polymer nanocomposites were characterized by Fourier transform infrared (FTIR), X‐ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X‐ray (EDX), transmission electron microscope (TEM), differential scanning calorimetry, thermogravimetric analysis, and ammonia gas sensing performance was also analyzed. FTIR and XRD studies revealed the attachment of Cu–Al2 O3 in the molecular chain of PIN. The presence of bright trapezoid channels and variation in morphology for different loading of nanoparticles were confirmed by SEM and TEM. The attachment of Cu–Al2 O3 nanoparticles in the PIN matrix was confirmed through EDX spectroscopy. The glass transition temperature and thermal stability of the composites were greatly enhanced with the loading of Cu–Al2 O3 . Enhancement in alternating current conductivity, dielectric constant and the current–voltage characteristics of the prepared composite revealed the semiconducting nature of the system with an increase in the loading of nanoparticles. Also, nanocomposite exhibited an excellent sensitivity and fast response to ammonia gas. The evaluated result of the present study suggested that Cu–Al2 O3 reinforced PIN hybrid is a good candidate for the fabrication of electrochemical devices. Abstract :